The Murchison Widefield Array delivers for Australian astrophysics - Tingay, Steven (Australian Institute of Physics, 2015)
The Murchison Widefield Array (MWA) is a low frequency (80-300 MHz) radio telescope that has recently become operational in remote Western Australia, a pristine radio quiet environment that allows the MWA to detect cosmic radio waves. I briefly illustrate the MWA's the early science outputs, revealing new information about the Earth's ionosphere and the Sun, enabling unique studies of our galaxy and its constituents, undertaking surveys of hundreds of thousands of other galaxies, and peering back in time 13 billion years to watch the birth of the first stars and galaxies after the Big Bang. The MWA is the first operational precursor for the multi-billion dollar Square Kilometre Array.